Endothelial dysfunction role in atherosclerosis pathogenesis - E. N. Vorobyeva (Кардиоваскулярная терапия и профилактика, 2006)
According to modern views, the key component in atherosclerosis pathogenesis is endothelial dysfunction (ED), manifesting in dysbalance between main endothelial functions: vasodilatation and vasoconstriction, proliferation inhibition and promotion, antithrombotic and prothrombotic, antioxidant and prooxidant functions. Endothelial effects are mediated through vasoactive agents’ release – vasodilatators (NO, prostacyclin, bradykinin) and vasoconstrictors (endothelin, free oxygen radicals, thromboxan A2 , angiotensin II). It has been demonstrated that virtually all atherosclerosis risk factors (RF) realize their negative effects via ED. Therefore, endothelial function parameters could be used as early atherosclerosis markers in individuals with atherosclerosis RF, at pre-clinical stage. Pathogenetic therapy, administered early or in already verified atherosclerosis, could improve patients’ prognosis substantially.